Population Fluctuation of Shisham Tree Hopper, Gargara mixta - Ali, M.S.; Azam, F.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
Study on seasonal population fluctuation of sissoo tree hopper, Gargara mixta (Membracidae : Homoptera) conducted in different growth stage of Dalbergia sissoo plantation at Pusa Farm of Rajendra Agricultural University, Pusa (Bihar) in 1993. The seasonal population of G. Mixta per leaf per stem and per branch of D. sissoo sapling varied from 0.59 to 4.08, 0.58 to Â·5.57 and 0.68 to 9.80 during morning and evening respectively. The maximum Â emperature showed significant and positive correlation with the population of G. mixta. Relative humidity has no significant effect.